IMPLEMENTATION OF AS-SHUKRU IN ISLAMIC EDUCATION (Efforts to Overcome the Psychosomatics of Modern Society) - Nasri Kurnialoh; Dielfi Mariana; Musayaroh; Solihin Sari (Jurnal Pendidikan Islam, 2026)
Abstract In today's world, stress and anxiety are serious mental health issues that frequently result in psychosomatic disorders. This study uses qualitative methodology and literature review techniques to investigate how the As-Gratitude value is applied in Islamic education. These results show that incorporating As-Gratitude into Islamic education greatly enhances emotional regulation and lessens psychosomatic symptoms. Frequent gratitude exercises aid in the restoration of physiological processes that have been hampered by prolonged stress. Future psychosomatic issues may be fully resolved by integrating the idea of As-Gratitude into Islamic education. Keywords: Islamic education, gratitude, psychosomatics, mental health, and contemporary society